Incidence of "oxidase-variable" strains of Aeromonas hydrophila. - Overman, T L (1979)
Certain strains of Aeromonas hydrophila are oxidase negative when grown on gram-negative selective and differential media. Of 100 strains of A. hydrophila examined, 8 were found to possess this characteristic. Information is provided on how to detect these common variants of A. hydrophila.